Characteristics of fire in high-speed train carriages. (January 2020) - Bi, Haiquan; Zhou, Yuanlong; Wang, Honglin; Gou, Qilin; Liu, Xiaoxia
With the rapid development of high-speed railways, safety hazards presented by train fires cannot be ignored. An effective design for protection against fire in high-speed trains is essential to ensure passenger safety. In this study, the cone calorimeter and ignition temperature tester were used to carry out combustion experiments on materials constituting the main components of the train. The heat release rate, smoke yield, CO yield, and ignition temperature of combustible materials were tested. Based on the experimental data of material combustion, a numerical model of the high-speed train carriage fire was simulated. The accuracy of the numerical simulation was verified by drawing a comparison with the full-scale train fire experiment in existing literature. The numerical simulation results revealed that when the fire source is present at the corner of the carriage end door, the fire develops to the maximum possible extent in approximately 25 min, with a peak heat release rate of approximately 38.4 MW. Increase in the carriage fire heat release rate and breakage of windows occur almost simultaneously. Improvement of the fireproof performance of windows can inhibit and delay the carriage fire development. For the flashover of carriage fire, the spread speed of the flashover area in the longitudinal direction inside the carriage is approximately 1.9 m/s. The end door area furthest from the fire source in the carriage has strong flashover, while the flashover in other areas is weak.